Terlipressin‐induced skin necrosis in cirrhotic patients—A case report and comprehensive literature review - Ashraf I. Ahmed (22045163) (2024)
The occurrence of terlipressin‐induced skin necrosis in cirrhotic patients is a rare but serious adverse event that warrants further investigation. Clinicians should be aware of this potential complication in cirrhotic patients receiving terlipressin therapy and closely monitor for any signs of skin necrosis. Early recognition and prompt intervention are crucial in preventing further complications and improving patient outcomes. Further research is needed to better understand the risk factors associated with terlipressin‐induced skin necrosis and to develop effective preventive strategies. Overall, healthcare providers should exercise caution when prescribing terlipressin to cirrhotic patients, weighing the potential benefits against the risks of this rare but significant adverse event. Terlipressin is commonly used to manage conditions related to portal hypertension, such as hepatorenal syndrome and esophageal variceal bleeding. Despite its therapeutic benefits, terlipressin can rarely lead to severe ischemic complications involving the skin vasculature, known as terlipressin‐induced skin necrosis. We present a 50‐year‐old male with cirrhosis and acute variceal bleeding who developed skin necrosis following terlipressin administration. We performed a comprehensive review of the literature by analyzing 18 case reports/case series comprising 22 cirrhotic patients with terlipressin‐induced skin necrosis. Among these individuals, we found a mean age of 51 years with a male predominance (78%). Further analysis showed that the onset of skin necrosis ranged from 2 to 5 days post‐terlipressin initiation, with bolus administration being predominant (85.7%). The underlying pathophysiological mechanisms of terlipressin‐induced skin ischemia are still elusive but primarily attributed to the vasoconstrictive and thrombogenic effects. Management involves terlipressin discontinuation and supportive care. Physicians should be aware of this potential complication in patients receiving terlipressin and closely observe for any signs of skin rash. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.9141